Studi Evaluasi Perencanaan dan Pengendalian Produksi dengan Pendekatan Economic Order Quantity (Eoq) pada Sistem Produksi Meja Lipat Karakter Solo - Sugeng Nugroho; Yuliana Ma’ruf Alfajri (At-Tauzi : Jurnal Ekonomi Islam, 2015)
Study Evaluation of Production Planning and Control with Economic Order Quantity Approach on Production System on Foldable Table Table Karakter Solo Production with the aim to get the efficiency difference in production planning and controlling on production system of Folding Table Karakter Solo which has been done by company with method of calculating Economic Order Quantity using descriptive research type with quantitative approach. Data collection uses observation data, interviews, and documentation. The results of the analysis prove that if the company uses Economic Order Quantity method in 2015 and 2016 in the purchase of raw materials, obtained raw material inventory savings of Rp. 3,567,600, - in 2015 and Rp. 3.629.200, - in 2016. Based on the results of the analysis, it is better that the production of Table Lipat Karakter Solo applies the Economic Order Quantity method by adding the supplier in determining the optimal quantity of raw material purchasing, thus minimizing the total cost incurred by the company every year.